International standards for social accountability: Between explanations and managerial apprehension (2019)
International Accountability Standards on environmental sustainability and social responsibility guide and evaluate the behavior of companies, so that they voluntarily adjust to certain regulatory principles. However, this voluntariness cannot be based solely on the idea that being ethical pays, since many of the social and environmental demands imply sacrificing profitability. The reflection presented here shows the existence of gaps in the justification of the principles that proclaim the standards, which condition their voluntariness and negatively impact both society and organizations themselves. Our discussion focuses on five of these standards, namely: Global Reporting Initiative (gri), Human Rights Compliance Assessment (hrca), the Ethos indicators manual, the Costa Rica Manual, and the Social Balance Guidelines of the Colombian National Industry Association (andi), which have been influential in Colombia and abroad. The purpose of this reflection is to show that the use and application of standards can lead to their manipulation by employers, placing them away from the moral and ethical obligations of a company with its stakeholders. © 2019, Universidad Nacional de Colombia. All rights reserved.